CIRI MAKROSKOPIS DAN SIFAT FISIS KAYU TRENGGULI (Cassia fistula .L) ASAL KABUPATEN KUPANG - Piter, Serlius; Manek, Luisa Moi; Davinsy, Rynaldo; Ranta, Fabianus; Adrin, Adrin (Tengkawang : Jurnal Ilmu Kehutanan, 2025)
The demand for commercial timber in Indonesian continue to increase, while the potential of production forests is decreasing. Therefore, an optimal forest management strategy is needed as a source of raw timber materials, including using quality plant types with fast-growing riaps. One of the potential species is (Cassia fistula L). or Trengguli which is widely found in the province of East Nusa Tenggara, especially Kupang City. However, information about the physical properties of Trengguli limited wood. The research purposes whose physical properties are determined and macroscopic characteristics of Trengguli wood at the base, middle, and end. Physical tested include moisture content, specific gravity, shrinkage, thickness expansion, and water absorption. Samples were taken from the field and tested in the laboratory using the Complete Random Design (RAL) method and analyzed using ANOVA. The results showed an average moisture content of 46%, specific gravity of 0.83, tangential shrinkage of 5.3-6.9%, radial 2.9-4.9%, and longitudinal 0.4-0,5%. Thick development after 2 hours ranges from 0.4-0.6% and after 24 hours 0.5-0.9%. Water absorption after 2 hours ranges from 0.7-1.6% and after 24 hours 1.4-2.7%. Based on ANOVA analysis, the position of the axial wood no real effect on physical properties. This study provides important information about the characteristics of Trengguli wood to support its use as a raw material for commercial wood. Keywords: Trengguli, macroscopic characteristics, physical properties, axial position, wood utilization. Abstrak Kebutuhan kayu komersial di Indonesia terus mengalami peningkatan, sementara hutan produksi terus berkurang. Oleh karena itu, strategi pengelolaan hutan yang optimal sangat diperlukan sebagai sumber kayu, termasuk melalui pemanfaatan jenis tanaman berkualitas dengan riap tumbuh cepat. Salah satu spesies yang berpotensi adalah (Cassia fistula L) atau Trengguli yang banyak ditemukan di Kota Kupang Provinsi NTT. Namun, informasi tentang sifat fisis kayu Trengguli masih terbatas. Tujuan dari penelitian ini ialah sifat fisis dan ciri makroskopis kayu Trengguli bagian pangkal, tengah, dan ujung. Sifat fisis yang diuji meliputi kadar air, berat jenis, penyusutan, pengembangan tebal, dan daya serap air. Sampel diambil dari lapangan dan diuji di laboratorium dengan metode Rancangan Acak Lengkap (RAL) dan dianalisis menggunakan ANOVA. Hasil penelitian menunjukkan rata-rata kadar air 46%, berat jenis 0,83, penyusutan tangensial 5,3-6,9%, radial 2,9-4,9%, dan longitudinal 0,4-05%. Pengembangan tebal setelah 2 jam berkisar 0,4-0,5% dan setelah 24 jam 0,4-0,7%. Daya serap air setelah 2 jam berkisar 0,9-1,0% dan setelah 24 jam 1,1-1,7%. Analisis ANOVA menjelaskan bahwa tidak terdapat pengaruh signifikan dari posisi aksial terhadap sifat fisis kayu Trengguli. Penelitian ini memberikan informasi penting tentang karakteristik kayu Trengguli untuk mendukung pemanfaatannya sebagai bahan baku kayu komersial. Kata kunci: Pemanfaatan kayu, posisi aksial, sifat makroskopis, sifat fisis, Trengguli